Patterns of Behavior and Medical Comorbidities in Down syndrome. Issue 3 (2nd July 2020) - Patel, Lina; Wolter-Warmerdam, Kristine; Hickey, Francis
ABSTRACT: Introduction: Children and young adults with Down syndrome can demonstrate increased behavior problems compared to their typically developing peers through childhood and adolescence. This study aims to: (1) identify common patterns of behaviors in children and young adults with Down syndrome and (2) assess potential medical comorbidities that could increase the risk for behavioral challenges. Methods: This retrospective, cross-sectional study identifies common patterns of behaviors in 378 children and young adults between 2 and 22 years of age with Down syndrome receiving care at a single medical center. Results: Composite scores were developed for each of the four study factors: (1) Externalization, (2) Apprehension, (3) Internalization, and (4) Harm/Unrest. Analysis of variance was conducted on the influence of comorbidities on the four factors. Results indicated that the impact of attention deficit hyperactivity disorder, Autism, feeding problems, heart defect, infantile spasms, obstructive sleep apnea, and prematurity on problematic behaviors were statistically significant. Conclusions: Our findings highlight the importance of addressing medical comorbidities to potentially reduce problematic behavior, while also identifying neurodevelopmental differences that result in categorical behavioral challenges for children and young adults with Down syndrome.